Sustainable Development For The Center Of Small Cities - Matra Anugraha; Arif Kusumawanto; Medy Krisnany (Departement of Architecture, Universitas Islam Indonesia, 2018)
As time goes by, cities have developed and grown to be crowded and densely populated area that lead to increasing energy consumption in cities. Thus, some guidelines need to be arranged to control the development of cities. Some of the guidelines are related to floor area ratio (FAR), operational energy, embodied energy, and mobility. Those aspects have strong influence on the consumption of energy in the cities in relation to the sustainability of the area future development. This is in line with the essence and objectives of sustainable cities. To calculate the guidelines, this research used experimental method by the means of computer simulation. The study utilized Rhinoceros with the plug in of Urban Modelling Interface (UMI), in which UMI is software that can simulate and calculate the four aspects correctly and accurately. The guidelines for city development are expected to provide comfortability of living to the community of cities during the development process.This research investigated about the development sustainability in Boyolali City. Based on visual observation, the buildings in the five ways intersection of Boyolali are not too crowded and dense with low storey buildings. This research found that the value of FAR is 0.17, the operational energy is 71.48 kWh/m2/year, the embodied energy is 150 kWh/m2/year, and the mobility is 80. The score of FAR still can be improved up to ten times and the value of operational energy, embodied energy, and mobility were still below maximum threshold.Keyword: Sustainable City, Simulation, Urban Modelling Interface.